Management and outcome in patients with post burn contracture - Rajan, Manu; Tyagi, Arnav; Dvivedi, Sanjay; Rawat, Kinnari A. V. (International Surgery Journal, 2018)
Background: Post burn contractures are distressingly common and severe in developing nations and considered as a significant problem in developed countries as well. Despite advances in the overall management of burn injuries, severe post-burn contractures continue to be a formidable foe for reconstructive surgeons in developing countries. Methods: The study was carried out in Department of Surgery, Himalayan Institute of Medical Sciences, SRH University, Swami Ram Nagar, Dehradun over a period of 12months. Cases of the post burn contractures attended in the O.P.D were included in the study. Results: Contracture release with split thickness skin grafting STSG in 25 (55.5%) cases. Contracture release with STSG with flap cover was performed in 7 cases (15.5%), contracture release with K wire insertion with coverage was performed in 8 cases (17.7%) and Z plasty was performed in 5 cases (11%). Conclusions: There have been major advances in burn care in the last three decades and the mortality rates have gone down significantly. The management has shifted to improvement of functional outcome and better quality of life. Proper planning of reconstructive procedures, rehabilitation, restoration to pre-injury status and return to society are the goals that the treating team hopes to achieve.